AN ANALYSIS OF STUDENTS’ ERROR IN USING DEGREES OF COMPARISON OF ADJECTIVE AT EIGHT GRADE STUDENTS OF SMP ISLAM AYATRA - Ummu Mashitho; Dyah Supraba Lastari; Abdul Rohim; Moh Iqbal Firdaus (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
The objective of this research was to know types of students’ errors and the most common or least type of students’ error in using degrees of comparison of adjective at eight grade students of SMP Islam Ayatra. Degrees of comparison is an important element of grammar that rules how to change the form adjective to show a comparison. The research used qualitative method. The participants of this research consisted of thirty students. The source of the data in this research was collected from students’ written test in using degrees of comparison of adjective. The result of this research stated that there were four types of errors, they are omission, addition, substitution, and permutation. The total of them is 485 errors. The highest percentage type of error was substitution with 54,64% (total frequency of errors was 265). And the lowest percentage type of error was addition with 2,06% (total frequency of errors is 10).